PERANAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN MASYARAKAT DI DESA TATELI INDUK KECAMATAN MANDOLANG KABUPATEN MINAHASA - Horman, Okniel (Universitas Sam Ratulangi, 2014)
Reformation era which aims to holdcorrection or alteration, the arrangement and arrangement back variousentertainments the social life of, nation and the country that better suit,conformable, and in line with the aim of the state as mandated in the openingconstitution of the Republic of Indonesia 1945 continuously tries to doproperly. Efforts to improve the developmentof rural areas in regional autonomy era now this is an important step andstrategic that need in observed in mobilise and diligently. For that thegovernment has determined to improve our motion village development in ruralareas. Hence the effort of development and empowerment of the village is animportant step to be done and improved by careful and effective. Through BPD the government hopes,invite and offer the opportunity as possible to the public to participate.Consultative board village as the receptacle of channeling collectors and theaspirations of the people who help the government village in performing andevelopment and have an important role because the village development veryuseful for all the village community. Community Tateli village there areseveral elements that can be used to run a course of development. Elements suchis that the community village Tateli solidarity having a strong, bothvertically and horizontally. Vertical in the sense of loyalty the communitywith the village administration and horizontally in the meaning of thesolidarity that binds the residents.Keywords:development, government, participate